Vulnerability assessment of Lingayen Gulf coastal areas due to sea level rise using geographic information system - Bandojo, Rosalie Luna (2003)
Sea level rise is a growing environmental concern especially along coastal areas. It is a fact that areas having difficulties coping with the present relative sea level rise will be the same areas that will be most vulnerable to future sea level rise. The use of Geographic Information System (GIS) facilitates the identification and quantification of vulnerable areas. Sector II of Lingayen coastal communities in pangasinan province was chosen as the study area. The flatness of the area and the presence of major rivers make it an ideal choice for vulnerability assessment. The area is also exposed to other hazards which will be enhanced should there be a significant increase in sea level in the near future. Using the Geographic Information System (GIS) technology vulnerable areas were identified using the tools for analysis. The raw data from field survey was processed using the GIS tool for contour generation, which delineates the two boundary conditions of 0.5- and 1.0-meter. The overlaying analysis was then used to identify and quantify areas that will likely be inundated. Tabulated reports were automatically generated by the system as a non-spatial result of the overlay analysis.
The implications of sea level rise were discussed in view of its impacts on the following areas: 1) effects on population, and 2)physical effects. Census data were incorporated to determine the population that will be displaced in year 2100. Topographic data was used to determine the vulnerability of some areas to geologic and hydrologic hazards that will be enhanced should there be a significant increase in sea level. The maps generated have shown that 7,666 hectares of land along the coast lie below the 0.5-meter contour. About 9,668 hectares of land will be inundated if seal level rises to 1.0 meter. Of the seven municipalities included in the study area, Binmaley Dagupan and Lingayen are the most vulnerable areas to sea level rise.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Sea level -- Philippines -- Lingayen Gulf; Coastal zone management -- Philippines -- Lingayen Gulf; Coast changes -- Philippines -- Lingayen Gulf; Geographic information systems -- Philippines -- Lingayen Gulf